Kreativitas Sutradara Fajar Nugros dalam Merepresentasikan Karakter Gepeng pada Film Biopic Srimulat: Hil yang Mustahal - Elanda, Asterina; Najmi, Maisaratun; Girsang, Nitasri Murawaty (Universitas Jember, 2024)
This research is discusses about the creativity that directors use in representing character who didn’t have much references The method used in this research is a qualitative, presented descriptively. Data was obtained through interviews and literature study. The results of research on director creativity in representing the character Gepeng in the film Srimulat: Hil yang Mustahal using the 4P’s of Creativity theory by person, process, press, and product. The results obtained show one of Fajar Nugros creativity by using make-up character and wardrobe to change’s the actor physical appearance to resamble Gepeng character, Fajar Nugros is classified as a good director based on Ken Dancyger classification of directors.